Characterization and comparative analysis of the plastome sequence from Justicia ventricosa (Lamiales: Acanthaceae). Issue 10 (3rd October 2021) - Zhou, Junchen; Du, Qing; Jiang, Mei; Liu, Shengyu; Wang, Liqiang; Chen, Haimei; Wang, Bin; Liu, Chang
Abstract: Justicia ventricosa is a characteristic ethnic herb commonly used to treat Orthopedic pains. Here, to confirm its phylogenetic position and to develop molecular markers that can distinguish different Justicia species, we obtained and analyzed the plastome of Justicia ventricosa. The plastome was sequenced using the Illumina HiSeq sequencing platform, assembled with NOVOPlasty, and annotated with CPGAVAS2. The genome has a circular structure of 149, 700 bp, containing a large single-copy region of 82, 324 bp, a small single-copy region of 17, 260 bp, and two reverse repeat regions of 25, 058 bp each. It encodes 112 unique genes, including 76 protein-coding genes, eight ribosomal RNA genes, and 28 transfer RNA genes. Twenty cis-splicing genes were found. In total, we predicted 19 microsatellite repeats and 13 tandem repeat sequences. For distributed repeats, four were palindrome repeats and five were direct repeats. To find the highly variable intergenic spacer (IGS) regions, we calculated the K2P distances for IGS regions from four Justicia species. The K2P values ranged from 6.11 to 57.82. The largest K2P distances were found for ccs A -ndh D, pet B -pet D, psb K -psb I, and ycf 4 -cem A. Phylogenetic analysis results showed that J. ventricosa was most closely related to J. leptostachya . To determine how Justicia species adapt to the environment, we performed selection pressure analysis. Nine genes were found to have undergone positive selection. Lastly, we performed a genome-wise DNA barcode prediction, seven pairs of primers were found. The results provide valuable information that can be used for molecular marker development and bioprospecting in Justicia species.